2020
DOI: 10.2478/prolas-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Wetland Species Rumex Hydrolapathum to Increased Concentration of Biogenous Heavy Metals Zn and Mn in Substrate

Abstract: Communicated by Mâris KïaviòðThe aim of the present study was to determine if individuals of Rumex hydrolapathum Huds native to saline wetlands are able to tolerate high concentration of biogenous heavy metals Zn and Mn in substrate and to accumulate high concentration of these metals in aboveground parts. Plant physiological status was monitored by using non-destructive analysis of chlorophyll and chlorophyll a fluorescence. R. hydrolapathum plants accumulated up to 1840 mg·kg -1 Zn and 6400 mg·kg -1 Mn in ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Plants were cultivated in an experimental automated greenhouse during the autumn–winter season. Procedures used for plant establishment and cultivation were the same as described previously for R. hydrolapathum [ 21 ]. Briefly, seeds were germinated in autoclaved commercial garden soil (Biolan, Eura, Finland) in closed containers placed under periodic light and temperature conditions in a plant growth cabinet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants were cultivated in an experimental automated greenhouse during the autumn–winter season. Procedures used for plant establishment and cultivation were the same as described previously for R. hydrolapathum [ 21 ]. Briefly, seeds were germinated in autoclaved commercial garden soil (Biolan, Eura, Finland) in closed containers placed under periodic light and temperature conditions in a plant growth cabinet.…”
Section: Methodsmentioning
confidence: 99%
“…In a coastal seawater-affected marsh, plants of Rumex hydrolapathum —an emergent macrophyte from flooded or permanently wet habitats [ 20 ]—showed high potential to accumulate both Na + and K + in leaves at levels significantly higher than those of adjacent plants [ 3 ]. This accession also displayed a high tolerance against biogenous heavy metals Zn and Mn, and extremely high metal accumulation potential in controlled conditions [ 21 ]. In the present study, three Rumex species with accessions from sea coast habitats ( Rumex hydrolapathum, Rumex longifolius and Rumex maritimus ) were chosen for salinity experiments in controlled conditions, and were compared to Rumex confertus , a cosmopolitan species not occurring in saline soils [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the characteristic specificity of the model plant species is that related to morphological characteristics of rosette-forming plants with continuously active leaf-forming apical meristem, like in R. hydrolapathum, which allow for clearly distinctive adaptive strategy in the case of soil chemical contamination. The surplus concentration of essential mineral elements (as K, Mn and Zn) or bulk amount of any unnecessary ions (as Na and Cl) primarily accumulate in the older leaves, followed by their accelerated senescence and stimulation of new leaf formation [44][45][46]. This type of development can be considered as part of an avoidance strategy, since the accumulation of potentially toxic elements does not occur in actively photosynthesizing leaves.…”
Section: Discussionmentioning
confidence: 99%
“…is a perennial high biomass-forming species naturally growing in wet and flooded habitats with a high disturbance frequency [43]. Tolerance to heavy metals, including Mn, in R. hydrolapathum has been mostly associated with physiological mechanisms, as the metals predominantly accumulated in older leaves, with appearance of characteristic visual signs of toxicity, followed by leaf senescence and dieback [44,45]. Along with it, formation of new leaves was stimulated.…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, R. hydrolapathum is characterized as only moderately salinity tolerant (indicator value 2 out of 5) [23]. Recently, we have shown that a R. hydrolapathum accession from a coastal wetland had high tolerance against biogenous heavy metals (Mn and Zn) [24] and that the accession had high tolerance against nitrate and nitrite as well as increased salinity tolerance [25]. It has been found that a general characteristic of R. hydrolapathum plants, which manifests in unfavorable conditions, is the ability to induce the aging process of older leaves and stimulate the formation of new leaves.…”
Section: Introductionmentioning
confidence: 99%